ESTIMASI POTENSI BIOMASSA DAN MASSA KARBON HUTAN TANAMAN Acacia crassicarpa DI LAHAN GAMBUT (Studi Kasus di Areal HTI Kayu Serat di Pelalawan, Propinsi Riau) - Yuniawati; Ahmad Budiaman; Elias (BRIN Publishing, 2011)
The role of forests as carbon sink and carbon store is undoubtedly important to reduce the carbon amount in the earth atmosphere thereby preventing greenbouse (GHG) effect that can induer the global warming. Among the varisar types of forest, peat swamp forest serves as the largest carbon store. A research bas been carried out at the fiber wond plantation forest comprising mostly Acacia crassicarpa species that grew on a peat land, at the Pelalawan sector, Rian Province. The research was to obtain allometric equatios that related the growth parameters of A. crassicarpa trees (Le tree diameter (D) and height either a total (tot) or branch free (Hbc)) to their growth products Le.biomess (W) and carbon mass (C). It was found that the best fitted and must representative allometric equations were consecutively IF= 0.398918D Hix (for estimating biomass patency) and C = 0.131D Htol